Bumble bee colony health is diminished in a mesotunnel enclosure planted with a cucurbit monoculture crop - Gauger, Lexi; Pulliam, Kathleen Fiske; Cherian, Yuuki; Garcia, Mateo; Morrison, Benjamin; Gonthier, David (Journal of Pollination Ecology, 2025)
The use of “mesotunnels” (mesh netting pest-exclusion structures) as a sustainable pest management strategy is increasing among organic vegetable growers. However, pollination management presents a challenge in this system, and little is known about how mesotunnels impact pollinator health. This study examines bee colony health in mesotunnels, using commercial Bombus impatiens colonies in cucurbit crop mesotunnels as a relevant model system in a two-year experiment. To assess colony-level health, we combined several variables into “colony health indices” that produce summary values of the somatic (related to pollination service delivery, including number of workers, worker and nest mass, and stored pollen and nectar), reproductive (related to sexual reproduction, including number of immatures, drones, and queen size), and overall colony health (including all variables in somatic and reproductive indices). We found that in 2023 B. impatiens colonies in a cucurbit mesotunnel foraging environment had worse reproductive health and overall health than free-foraging colonies, but performed similarly in their somatic health. In several measurements, colonies from mesotunnels performed similarly to colonies with no foraging access. Our results suggest that commercial colonies in mesotunnel environments are not compromised in their potential to provide crop pollination services, but are compromised in their ability to reproduce and persist year-over-year. Our colony health indices could be adapted to assess the status of reproduction and ecosystem service delivery for social bees.